Report on effects of adding metal additives to aluminum oxide - Chang, Jun Hua. (2012)
Aluminum oxide has been widely used in the electronics industry as a packaging and insulating material. For electronic packaging of harsh environment, which is in high temperature and extreme high atmospheric pressure, materials with high hardness, high fracture toughness and low thermal conductivity are desired. In this report, we study the effect of addition of metal impurities to the properties of aluminum oxide. Metal and aluminum oxide powders were mixed and sintered, and the samples were tested for their porosity, hardness, thermal conductivity and dielectric constant. Scanning Electron Microscopy and X-Ray Diffractography were conducted to understand the particle sizes and the phases present. The addition of metal additives differs in the effect in the properties of aluminum oxide, but the effect generally ties in with porosity. Further tests were also conducted with increased amount of additives and sintering hours. Increasing the amount of additives lowered the thermal conductivity but decreased hardness and dielectric constant. The addition of iron with longer sintering hours brought about the greatest improvement to the hardness and thermal conductivity, but it also increased the dielectric constant.